Traditional Markets in the Sharia Economic Perspective: Exploring Structural Changes and Social Value Reconstruction in Modern West Sumatra - Ramadhan, Rifki; Fahlefi, Rizal (El-kahfi | Jurnal Ekonomi Islam, 2025)
This research aims to analyze the relevance and competitiveness of traditional markets in West Sumatra from the perspective of sharia economics, with a focus on digital transformation, merchant innovation, and inherent social-spiritual values. The method used is a Systematic Literature Review (SLR) of 12 selected studies from the 2015–2025 period, which includes field research, case studies, policy studies, and literature supporting sharia economics. The thematic synthesis identifies four main themes: (1) the socio-economic structure and social role of traditional markets; (2) transformation and modernization challenges; (3) actualization of sharia economic value in traders' practices; and (4) the direction of empowerment and repositioning of digital-based markets and sharia cooperatives. The results show that traditional markets are still the backbone of the people's economy, but face pressure from modern markets and global digitalization. Limited digital adaptation, weak sharia institutions, and changes in consumer behavior are the main challenges. Empowerment strategies based on sharia digitalization, the establishment of sharia cooperatives, and strengthening market ethics are suggested so that traditional markets remain relevant, competitive, and socially just in accordance with the principles of sharia maqashid. This study makes a theoretical and practical contribution to the development of local economic policies based on Islamic values.